SOSIALISASI GEJALA SERANGAN HAMA DAN PENYAKIT TERHADAP TANAMAN PADI SERTA CARA PENGENDALIANNYA DI DESA PEMATANG BALAM, KECAMATAN HULU PALIK, KABUPATEN BENGKULU UTARA - Andreani Andreani Kinata; Eny Rolenti Togatorop; Dia Novita Sari; Parwito Parwito; Edi Susilo; Novita Hamron (Fakultas Pertanian, 2023)
The cultivation of rice (Oryza sativa) cannot be separated from the threat of major pests and diseases that often attack these plants. If the pest attack is not properly controlled, it can reduce the productivity of the rice plant. The purpose of this community service activity is to provide socialization or counseling to farmers in Pematang Balam Village, Hulu Palik District, North Bengkulu Regency to be able to recognize the symptoms of pest attacks and the main diseases of rice plants and then apply appropriate, fast and accurate controls. The method used is a form of counseling. This counseling activity was given to 30 farmer members in the village of Pematang Balam. The results obtained during the community service activities were 1) the participants were enthusiastic about the material provided, seen from the many questions asked by the participants both in the form of the characteristics of pests and how the symptoms were caused by these pests and diseases, 2) in general the participants already knew chemical pest control methods. The conclusions of this community service activity are 1) the service participants and all Pematang Balam Village officials welcomed this service program. 2). the implementation of the service program went quite well and smoothly and the participants were quite enthusiastic. 3). The farmers and village officials of Pematang Balam hope that there will be a follow-up service program with another theme to add to and open up scientific knowledge in the community.